2015
DOI: 10.1007/978-3-319-26784-5_11
|View full text |Cite
|
Sign up to set email alerts
|

The Robot Crawler Number of a Graph

Abstract: Information gathering by crawlers on the web is of practical interest. We consider a simplified model for crawling complex networks such as the web graph, which is a variation of the robot vacuum edge-cleaning process of Messinger and Nowakowski. In our model, a crawler visits nodes via a deterministic walk determined by their weightings which change during the process deterministically. The minimum, maximum, and average time for the robot crawler to visit all the nodes of a graph is considered on various grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…where the case q ≤ j follows immediately from (12) (since 2/j ≤ 1 q 2 √ q/j), and the case q ≥ j is trivially true (since the right-hand side of (13) is greater than 1). Combining (11) and (13) together and using the fact that H holds a.a.s., we conclude that…”
Section: Relationship Between G N M and G N M−oldmentioning
confidence: 99%
See 4 more Smart Citations
“…where the case q ≤ j follows immediately from (12) (since 2/j ≤ 1 q 2 √ q/j), and the case q ≥ j is trivially true (since the right-hand side of (13) is greater than 1). Combining (11) and (13) together and using the fact that H holds a.a.s., we conclude that…”
Section: Relationship Between G N M and G N M−oldmentioning
confidence: 99%
“…In [11], a simplified model for crawling complex networks such as the web graph was proposed, which is a variation of the robot vacuum edge-cleaning process introduced earlier by Messinger and Nowakowski [28]. In particular, it was shown that a.a.s.…”
Section: Lower Boundmentioning
confidence: 99%
See 3 more Smart Citations